FLIPPING THE SWITCH ON ALTERNATIVE ENERGY? (Utah Environmental Law Review; Vol 29 No 1 (2009), 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Note: The following is a synopsis of a talk given at the Stegner Center in February 2008. This article has been shortened and the visual slides and charts presented in that discussion are not included.   Thank you to the Stegner Center for inviting me here today to present a utility perspective on climate change. The presentations made during this conference do much to explain the challenges we face in connection with climate change and to identify potential solutions. It is clear that as a society, we have the necessary technological abilities to address these challenges. However, for these abilities to have a substantive impact, there must be timely and common sense policies on climate change which will allow utilities to focus on specific, unambiguous objectives. These policies must take into account practical considerations related to our need for energy security. My discussion here today is not to engage in the technical, political or ideological debates concerning climate change. Rather, my goal is to identify some of the practical considerations that are integral to long range resource planning and the challenges presented in that context from the perspective of an electric utility, and to highlight some of the practical resource and demand side alternatives available today.